Analisis Indeks Massa Tubuh Anak Balita Pada Kegiatan Bina Desa di Desa Teluk Kapuas - Naomi Debataraja; Aditya Nugraha Pratama; Anisa Putri Ayuni; Disya Recita Amalia; Lyra Mauditia; Resti Arsanti; Reyana Hilda Arti; Rifkah Alfiyyah Sary; Tarisa Umairah; Yumna Hanum Salsabila; Steven; Rahmawati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Stunting is one of the focus problems in the Kubu Raya Regency. In 2021, the stunting rate in West Kalimantan reaches 17.75% and Kubu Raya Regency is 7.87%. The village development activity is one of the independent learning programs for the independent campus of FMIPA, Tanjungpura University. This activity was carried out for five months in Teluk Kapuas Village. This activity aims to collect data to determine the level of nutritional status of children and toddlers in Teluk Kapuas Village. Data collection was carried out by measuring and recording weight and height when Posyandu activities were carried out and obtained 90 samples of children and toddlers. It was known that from 90 samples of toddlers, 1,11% had poor nutritional status and 8,89% had poor nutritional status. The results of the independent t test showed that the average BMI of toddlers and girls was 14,84 and that of boys was 16,06. From the paired t test, it is known that there are significant differences in the average height and weight of children and toddlers in the month before and after carrying out stunting education. This shows that stunting education encourages growth in children in Teluk Kapuas Village.